2013
DOI: 10.1371/journal.pone.0065763
|View full text |Cite
|
Sign up to set email alerts
|

LY2405319, an Engineered FGF21 Variant, Improves the Metabolic Status of Diabetic Monkeys

Abstract: Fibroblast growth factor 21 (FGF21) is a novel metabolic regulator that represents a promising target for the treatment of several metabolic diseases. Administration of recombinant wild type FGF21 to diabetic animals leads to a dramatic improvement in glycaemia and ameliorates other systemic measures of metabolic health. Here we report the pharmacologic outcomes observed in non-human primates upon administration of a recently described FGF21 analogue, LY2405319 (LY). Diabetic rhesus monkeys were treated subcut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
156
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(174 citation statements)
references
References 23 publications
(39 reference statements)
12
156
2
Order By: Relevance
“…For example, while FGF21-class molecules readily normalize blood glucose levels in mouse models of obesityinduced insulin resistance [14], [15], [16], only a modest glucose lowering effect was observed in human patients with type 2 diabetes [28], [29]. In addition, FGF21-analogs strongly suppress food intake in NHPs [28], [32], while a mild increase in food consumption occurs in mice [15], [16]. Hence, although FGF21-class molecules induced robust weight loss both in NHPs and in diet-induced obese mice, the mechanism of weight loss in NHPs appears to be related to reduction in food consumption [28], [67], while thermogenesis primarily drives weight loss in mice.…”
Section: Metabolic E昀fects In Nhps and Humansmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, while FGF21-class molecules readily normalize blood glucose levels in mouse models of obesityinduced insulin resistance [14], [15], [16], only a modest glucose lowering effect was observed in human patients with type 2 diabetes [28], [29]. In addition, FGF21-analogs strongly suppress food intake in NHPs [28], [32], while a mild increase in food consumption occurs in mice [15], [16]. Hence, although FGF21-class molecules induced robust weight loss both in NHPs and in diet-induced obese mice, the mechanism of weight loss in NHPs appears to be related to reduction in food consumption [28], [67], while thermogenesis primarily drives weight loss in mice.…”
Section: Metabolic E昀fects In Nhps and Humansmentioning
confidence: 99%
“…Hence, although FGF21-class molecules induced robust weight loss both in NHPs and in diet-induced obese mice, the mechanism of weight loss in NHPs appears to be related to reduction in food consumption [28], [67], while thermogenesis primarily drives weight loss in mice. The weight-loss induced by FGF21-class molecules in NHPs is accompanied by improvements in various cardiometabolic lipid factors [28], [30], [31], [32]. Whether or not FGF21 activates BAT thermogenesis in NHPs has yet to be determined.…”
Section: Metabolic E昀fects In Nhps and Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…Truncation of N termini (NT) by six or more residues, or C termini (CT) by two or more residues, decreased in vitro potency more than 10-fold, suggesting that potent functional activity was derived from both termini of FGF21 (Micanovic et al, 2009;Yie et al, 2009). In diabetic animal models and patients with type 2 diabetes, recombinant fibroblast growth factor 21 (rFGF21) and its analogs demonstrated dose-dependent reductions in low-density lipoprotein cholesterol, apolipoproteins, fasting triglycerides, fasting insulin, and body weight, as well as dose-dependent elevations of high-density lipoprotein cholesterol and adiponectin (Adams et al, 2013;Gaich et al, 2013;Kharitonenkov et al, 2013;Smith et al, 2013). Although dose-dependent reductions in blood glucose have been observed in diabetic rodent and nonhuman primate models, thus far only a trend toward lower fasting blood glucose has been observed in human clinical studies (Gaich et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting that both FGF19 and FGF21 show beneficial effects on obesity and insulin sensitivity (11)(12)(13)(14). Recent studies revealed that a synthetic FGF21 analog improves lipid metabolism in obese humans and monkeys with type 2 diabetes (15,16). These reports suggest FGF19 and FGF21 are attractive therapeutic targets for obesity and diabetes.…”
mentioning
confidence: 99%